2015
DOI: 10.1177/0957650915591906
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study on aerodynamic optimization of part-span connectors in the last stage of a low-pressure industrial steam turbine

Abstract: Industrial steam turbines are operated over an extremely wide range of operating conditions. In order to ensure safe turbine operation, even in blade resonance condition, conical friction bolts are mounted between blade reinforcements of adjacent last stage low-pressure blades. These part-span connectors (PSC) provide blade damping and coupling. However, additional losses are generated, which affect the performance of the turbine. In this paper, a numerical and experimental study on aerodynamic optimization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Investigations of the part-span connector under subsonic flow conditions have been carried out by Bruggemann et al [1], Bin Li et al [2] and by Häfele et al [3,4]. These works by various research teams around the world showed that part-span connectors induce vorticial structures, cross flow, and increased losses.…”
Section: State Of the Artmentioning
confidence: 99%
“…Investigations of the part-span connector under subsonic flow conditions have been carried out by Bruggemann et al [1], Bin Li et al [2] and by Häfele et al [3,4]. These works by various research teams around the world showed that part-span connectors induce vorticial structures, cross flow, and increased losses.…”
Section: State Of the Artmentioning
confidence: 99%
“…Traupel 15 ) are normally used to determine the efficiency losses. More detailed numerical and experimental studies on the flow impact of part-span connectors in LP steam turbine blading have recently been published by Ha¨fele et al [16][17][18] Depending on the size and position of the elements, an efficiency decrease of several percentage points must be expected. 17…”
Section: Damping Elements Developmentmentioning
confidence: 99%
“…The test rig setup is shown in Figure 2. Further details can be found in Ha¨fele et al [16][17][18] The turbine is equipped with various temperature and pressure probes for a complete thermodynamic evaluation. Moreover, strain gauges are applied to several moving blades of the rows.…”
Section: Test Rigmentioning
confidence: 99%